Teaching Writing Skills in University Large Classes In Pakistan: Issues, Challenges and Solutions - Amjad Ali Jokhio; Syed Shakir Raza; Muhammad Younus; Ashfaq Hussain Soomro (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2020)
This study aims to investigate the concept of a large class, challenges and issues faced by the teachers while teaching writing skills courses in large classes along with the strategies they use in order to cater to the problems. Therefore, in-depth interviews with nine private and public sector university teachers were conducted. The thematic analysis of the data revealed that a large class, in the Pakistani context, consists of 30 to 35 students and teachers particularly face the problems in assessment, giving feedback, ensuring individual attention, maintaining discipline, and controlling noise factor, etc. The assessment and feedback issues can be catered to by using peer assessment and peer feedback as they are viable strategies to deal with the large writing classes. In order to reduce the noise factor, some related activities can be practised to ensure maximum involvement of learners and ultimately, it reduces the disruptive noise. Identification of students in terms of their behaviour and seriousness towards learning paves the way for choosing appropriate teaching techniques which in turn helps to manage large writing classes having mixed ability students to achieve objectives of the course.